KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DENGAN WORKED EXAMPLE: SYSTEMATIC LITERATURE REVIEW - Andini, Pungky Ayu; Novaliyosi, Novaliyosi; Santosa, Cecep Anwar Hadi Firdos (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This research aims to analyze worked examples in mathematics learning and mathematical problem solving abilities with worked examples from the 2019-2024 period. This research uses Systematic Literature Review (SLR) sourced from Google Scholar. 21 articles were collected, 15 articles related to worked examples in mathematics learning and 6 articles related to mathematical problem solving abilities using worked examples. The results obtained by using worked examples in mathematics learning can minimize students' cognitive load, help teachers teach new material concepts and deepen students' understanding of the concepts they have learned, then they can improve mathematical abilities, then worked examples are used to develop learning modules and LKPD or worksheets. Using worked examples improves mathematical problem solving abilities. Apart from that, the ability to solve problems using worked examples can be combined with other learning such as combining it with tracing gestures, differentiation and integrated worked examples